¿Ser taxista es un factor de riesgo cardiovascular? Análisis del perfil lipídico e IMC - Tapia, Mercedes (2017)
Context: there are multiple modifiable risk factors involved in the onset of cardiovascular events, such as high levels of low density lipoprotein, decreased high density lipoprotein, high blood pressure, smoking, alcohol consumption and sedentary lifestyle.Objective: to relate the body mass index with the lipid profile in taxi drivers, in addition to knowing the habits and related life practices.Subjects and methods: observational, cross-sectional, epidemiological study in which 112 participants were evaluated, 89 (70.46%) men and 23 (20.53%) women, with an age between 19 and 68 years of age; weight, height, BMI, blood pressure were measured and the lipid profile was determined.Results: 32 individuals have normal weight, while 60 have obesity, 19 obesity type 1 and 1 obesity type 2. Conclusion: taxi drivers have a high prevalence of obesity. The results of this study will serve as a basis for the design of educational interventions focused on motivation and self-care to prevent overweight and predict the risk of suffering a cardiovascular event.